Thermodynamic and kinetic insights into azo dyes photocatalytic degradation on biogenically synthesized ZnO nanoparticles and their antibacterial potential - Abu Bakar Siddique; Muhammad A. Shaheen; Azhar Abbas; Yasir Zaman; Mohammed A. Bratty; Asim Najmi; Ali Hanbashi; Muhammad Mustaqeem; Hassan A. Alhazmi; Zia ur Rehman; Khalid Zoghebi; Hatem M.A. Amin (Heliyon)
The extensive use of azo dyes in textile and pharmaceutical industries pose significant environmental and health risks. This problem requires to be tackled forthwith through a cheap, environmentally friendly and viable approach to mitigate water pollution. In this context, the green synthesis method was used for synthesis of ZnO NPs. These biogenic ZnO NPs were characterized by UV–Vis and Fourier transform infrared spectroscopy (FTIR), powder X-ray diffraction (PXRD), high-resolution transmission electron microscopy (HR-TEM) coupled with energy-dispersive X-ray (EDX), dynamic light scattering (DLS) and Zeta potential (ZP) analysis. The characteristic bandgap energy (3.02 eV), crystallite size (18.6 nm), particle size (84 nm), hydrodynamic diameter (101 nm) and ZP (−31.5 mV) all indicated the successful synthesis of the stabilized NPs, which have an absorption edge at 373 nm. Based on the responsive energy band gap to visible light, these NPs demonstrated promising photocatalytic activity for the degradation of toxic dyes with efficiencies of 82.2 and 87.5 % for of methylene blue (MB) and methyl orange (MO), respectively, in only 2 h of sunlight exposure. To evaluate the reaction kinetics and thermodynamic parameters including the activation energy and rate constant, the degradation process was conducted at various temperatures. The effect of temperature showed the highest rate constant values of 0.022 and 0.025 min−1 at 90 °C, and activation energies of 4.1 and 3.8 kJ mol−1 for MO and MB, respectively. A possible degradation mechanism was proposed based on results of the radical scavenging experiments. The photocatalyst showed recyclability for five consecutive cycles with a simple regeneration. CMFE@ZnO NPs have also exhibited great antibacterial potential by inhibiting the growth of Gram-positive (S. aureus (13 mm) and B. subtilis (14 mm)) and Gram-negative (E. coli (17 mm) and P. multosida (15 mm)) bacterial strains. As a result, these CMFE@NPs may have great commercial importance in reducing the concentration of azo dyes and drug-resistant bacteria in textile and pharmaceutical industry effluents.